2017
DOI: 10.1371/journal.pcbi.1005681
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulation strategy, feedback timing and hemodynamic properties modulate learning in a simulated fMRI neurofeedback environment

Abstract: Direct manipulation of brain activity can be used to investigate causal brain-behavior relationships. Current noninvasive neural stimulation techniques are too coarse to manipulate behaviors that correlate with fine-grained spatial patterns recorded by fMRI. However, these activity patterns can be manipulated by having people learn to self-regulate their own recorded neural activity. This technique, known as fMRI neurofeedback, faces challenges as many participants are unable to self-regulate. The causes of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 38 publications
2
42
0
Order By: Relevance
“…There are in general two ways regarding how often feedback scores are presented during the fMRI neurofeedback training; continuously and intermittently [50–52]. Here, continuous feedback refers to the feedback that is presented continuously during the neurofeedback training, and the feedback score changes every time the brain activation is measured by fMRI, for instance, every 2 sec.…”
Section: Four Significant Aspects Of Progress Of Fmri Neurofeedbackmentioning
confidence: 99%
See 2 more Smart Citations
“…There are in general two ways regarding how often feedback scores are presented during the fMRI neurofeedback training; continuously and intermittently [50–52]. Here, continuous feedback refers to the feedback that is presented continuously during the neurofeedback training, and the feedback score changes every time the brain activation is measured by fMRI, for instance, every 2 sec.…”
Section: Four Significant Aspects Of Progress Of Fmri Neurofeedbackmentioning
confidence: 99%
“…It is controversial which type of feedback is more effective. A recent computational study [52] has indicated that for successful fMRI neurofeedback learning, temporal characteristics of fMRI signal need to be considered since the fMRI signal is delayed and blurred in time relative to underlying neural activities due to slower hemodynamics than neuronal firing. These characteristics form a temporal credit assignment problem [53] in which participants need to associate their neural activities at a certain time point with a feedback score that reflects the delayed and blurred fMRI signals.…”
Section: Four Significant Aspects Of Progress Of Fmri Neurofeedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…The "modelling" phase can involve experimental brain-imaging studies and comparison of different neurofeedback protocols in healthy participants or patients, but also exclusively rely on modelled data obtained from simulations. It has recently been shown that simulation studies can be useful for the assessment of feasibility of real-time fMRI neurofeedback protocols (5). The next stage would be an "exploratory trial", which could employ an adaptive design, in order to optimize the intervention and assess its feasibility in the targeted patient population.…”
Section: When Is No Control Acceptable?mentioning
confidence: 99%
“…Admittedly, neural reinforcement is still a new intervention and few studies on its mechanisms of action are available (see (Oblak et al, 2017;Shibata et al, 2019) . Our current results suggest the interesting possibility that the changes in the regulatory action of the vlPFC and vmPFC might have led to the decrease in amygdala and skin conductance reactivity.…”
Section: Discussionmentioning
confidence: 99%